Dermatophytes and other associated fungi isolated from ringworm lesions of camels - Mahmoud, A L (Folia microbiologica, 1993)
Among 75 camels showing skin lesions, 48% were positive for fungal infection. The younger individuals were more susceptible to this infection. Sixteen species belonging to nine genera of keratinophilic and cycloheximide-resistant fungi were recovered from diseased camels. Trichophyton, Microsporum and Chrysosporium were the most common genera. T. verrucosum appeared to be the main cause of ringworm in small camels while T. mentagrophytes infected older ones. Camel skin presents a suitable habitat for the growth of some dermatophytes and other potentially pathogenic fungi.
Keywords: tinea; Species Specificity; zdroje nemoci; Egypt; kůže; Tinea; Disease Reservoirs; Age Factors; věkové faktory; Animals; druhová specificita; velbloudi; Arthrodermataceae; zvířata; Skin; Camelus